FRI0093 A Systematic Analysis of the Safety of Prescribing of Anti-Rheumatic, Immunosuppressive and Biologic Drugs in Men Trying to Conceive. (10th June 2014) - Panchal, S.; Flint, J.; van de Venne, M.; Piper, M.; Hurrell, A.; Cunningham, J.; Gayed, M.; Schreiber, K.; Anthanari, S.; Nisar, M.; Williams, D.; Khamashta, M.; et al.
Abstract : Background: Prescribing of anti-rheumatic and immunosuppressive drugs in men with active rheumatic disease trying to conceive is required to control disease activity. This increases the chance of successful conception. However it is complicated by concerns regarding the safety of these drugs. They arise from safety information based mainly on experimental and animal studies as human data is limited. Previous systematic reviews have identified a risk of oligospermia with sulfasalazine and gonadal toxicity with cyclophosphamide in men trying to conceive, as well as theoretical concerns for leflunomide and biologics. We have undertaken a systematic review to update information on this subject. Objectives: This systematic review aims to update information on the safety fo prescribing these drugs in men trying trying to conceive. Methods: A systematic search of PubMed and Embase was carried out using relevant keywords for pregnancy, men, conception and drugs commonly prescribed in patients with rheumatic disease from 1966 onwards. The drug categories included analgesics, disease modifying anti-rheumatic drugs, biologics and steroids. Review articles and non-English language papers were excluded. Results: 21 studies were selected for detailed review, describing relevant drug use in men with rheumatic disease, inflammatory bowel disease, post-transplantation, psoriasis, multiple sclerosis and leukaemia. The studies included 3 case reports, 4 case series, 10 cohort studies and 1 case-controlled study. These studies identified 2214 drug exposures (705 NSAIDs, 517 steroids, 343 azathioprine, 287 ciclosporine, 100 methotrexate, 120 sulfasalazine, 44 etanercept, 66 infliximab, 13 hydroxychloroquine, 11 rituximab, 6 adalimumab, 2 leflunomide) in 1963 men trying to conceive, leading to 2112 pregnancies. There were limited reports of the effects upon fertility (in 133 men) and one retrospective questionnaire study 1 of 30 men taking azathioprine reported an increased rate of infertility (>1yr to conception) of 15.2% vs 8.3% of controls. The confounding effects however, of underlying (Crohn's) disease and the possibility of female infertility, were a limitation of this study. Of the 1778 live births, 33 congenital malformations were reported which were not specific to any drug. In the remaining 78 pregnancies that miscarried, the precise number of elective terminations was not stated in all studies. Conclusions: This systematic review did not find an increased risk of adverse pregnancy outcomes in partners of men taking anti-rheumatic, immunosuppressive and biologic drugs whilst trying to conceive. However there remains insufficient evidence to advocate the safe use of these drugs. This information however, is useful when counselling men of potential risk particularly after accidental conception. References: Teruel C et al. Outcomes of Pregnancies Fathered by IBD patients exposed to thiopurines. The American Journal of Gastroenterology 2010; 105:2003-2008 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4289